Renal Dysplasia in a Free-Living Giant Anteater Cub (Myrmecophaga tridactyla) - Ultrasonographic and Tomographic Aspects - Neri Jaworski, Lorena Tavares de Brito; Borba, Jullia de Pinho; Rezende, Bianca Costa; Lopes, Jéssica Martins; Morgado, Thais Oliveira; Néspoli, Pedro Brandini (Acta Scientiae Veterinariae, 2021)
Background: Renal dysplasia is a congenital disorder that occurs during differentiation of the renal parenchyma or as a consequence of a functional and/or structural obstruction of the lower urinary tract. In wild animals, this pathology has been reported in cynomolgus monkeys (Macaca fascicularis), golden hamsters (Mesocricetus auratus) and African elephants (Loxodanta africana). However, there are no reports of the disease in the giant anteater (Myrmecophaga tridactyla). Thus, this paper describes a case of renal dysplasia in a free-living giant anteater cub, which was sent to the wild animal clinic of the Federal University of Mato Grosso (UFMT) in Cuiabá, MT, Brazil. Case: The rescued animal had a good body condition score and clinical parameters within the normal range for the species. After a routine clinical evaluation, the anteater cub was subjected to radiography and ultrasound tests. Blood tests, serum tests for hepatic and renal profiles, urinalysis, urinary protein creatinine ratio, and chest X-rays did not reveal significant changes. However, the abdominal ultrasound examination revealed a volumetric loss of about 1.17 cm in length in the left kidney, and a renal length to aortic artery diameter ratio of approximately 2.8. This kidney showed irregular contours, loss of corticomedullary demarcation, with preserved echogenicity and cortical echotexture. The right kidney showed the standard size of the species, with a length of approximately 3.08 cm. In view of the suspicion of renal dysplasia, a contrast-enhanced CT scan was performed in order to assess the dynamics of uptake and excretion of the contrast medium in the affected kidney and in the ipsilateral collecting system. An examination of the tomographic images indicated that the volume of the left kidney was reduced, isodense in relation to the right kidney, with discrete and homogeneous uptake in all phases after administration of the contrast medium, no occurrence of nephrogram and pyelogram phases, or any detection of contrast in the corresponding ureter. Discussion: Giant anteaters (Myrmecophaga tridactyla) are animals classified as a species vulnerable to extinction. Today, most research involving this species focuses on its ecology, behavior, diet, morphology and parasitology, but little is known about the imaging aspects of the species or about congenital changes such as renal dysplasia. Although the definitive diagnosis of this pathology depends on a histopathological examination, the same diagnosis can be made with a wide margin of safety by assessing the epidemiological aspects and the dynamics of renal uptake of the contrast medium through computed tomography. In this analysis, both vascularization and renal filtration capacity can be assessed. Thus, based on CT imaging, it was concluded that this was a case of renal dysplasia, since the left kidney showed a discrete homogeneous uptake stable in both the arterial and venous phases, without producing any accumulation of contrast medium in the pelvic region or the collecting system, proving to be completely nonfunctional. These findings differ from cases of renal hypoplasia, which, although they reduce renal volume, do not cause structural changes in the renal parenchyma or disturbances in the filtration dynamics of contrast media. They also differ from cases of acquired chronic nephropathy, since, albeit associated with reduced renal volume and changes in renal filtration dynamics, they produce different parenchymal ultrasound changes that usually occur in elderly animals and generally produce bilateral lesions.